Needs Analysis of Designing Course Materials for Primary Education Studies (PES) Students of Federal College of Education, Yola Adamawa State of Nigeria Learning Arabic for Specific Purposes (ASP) - Jabir Abdullah, (JCTE, 2023)
This paper carried out needs analysis with the aim at shedding light on the necessity for the innovative course materials that will be designed and developed for the effective teaching and learning of the Arabic courses, specifically for the learners in the department of Primary Education Studies (PED).The population of the study comprised of one hundred and seventy five (175) NCE II students, who took PED 219 (Arabic in Primary Education 11), in first semester NCE II as well as PED 126 ( Arabic in Primary Education 1) in their second semester NCE I 2017/2018 academic session. One hundred and twenty (120) students were selected using simple random sampling.